Percutaneous catheterization technique for perfusion in thick venous trunks - Muchada, Raúl; Artucio, Hernán; Correa, Humberto; Mazza, Norma; Grases, Hugo (Cirugía del Uruguay, 1976)
Twenty percutaneous cei:itral vein catheterizations were perforn:ied on sixteen patients during a period of two months. The technique implies the use of a lead52 ing flexible metallic chuck, which permits the use of catheters of a gauge larger thant the ones which are introduced through a puncture needle. Theri;, were no complications but for a puncture of the carotide artery without further consequences, and a local infection in the cutaneous orífice. The method permits quick catheterizations, repeated without. diminishing the "venous capital" of the patient, and with very little material. High flows can be used, even for hypertonic solutions, without risking chemical phlebitis, and reliable control of hemodynamic parameters (C.V.P.) can be obtained.